2000
DOI: 10.1128/jcm.38.3.1250-1254.2000
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Analysis of Non-M-Typeable Group A Streptococcus Isolates from a Thai Population in Northern Thailand

Abstract: Infection with group A streptococci (GAS) can lead to the development of severe postinfectious sequelae such as rheumatic fever (RF). In Thailand, RF and rheumatic heart disease (RHD) remain important health problems. More than 80% of GAS circulating in this population are non-M antigen typeable by conventional M serotyping methods. In this study, we determine the M protein sequence types of GAS isolates found in northern Thailand. The emm genes from 53 GAS isolates, collected between 1985 and 1995 from indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(7 citation statements)
references
References 13 publications
0
6
1
Order By: Relevance
“…3,29 In some tropical regions with a high incidence of RF, GAS pyoderma is endemic yet rates of GAS pharyngeal carriage and symptomatic pharyngitis are low. 2,3,5,62 Should GAS skin infection be implicated in RF pathogenesis, a new approach to primary prevention would potentially be opened.…”
Section: Primary Preventionmentioning
confidence: 99%
“…3,29 In some tropical regions with a high incidence of RF, GAS pyoderma is endemic yet rates of GAS pharyngeal carriage and symptomatic pharyngitis are low. 2,3,5,62 Should GAS skin infection be implicated in RF pathogenesis, a new approach to primary prevention would potentially be opened.…”
Section: Primary Preventionmentioning
confidence: 99%
“…Currently, more than 170 emm types and 750 emm subtypes of GAS have been described [3]. Studies of GAS emm-typing distribution performed worldwide, have shown a differing distribution of emm types in different countries and regions [4][5][6][7]. SAgs are thought to contribute to the pathogenesis of severe GAS infections by virtue of their potent immunostimulatory activity and the distribution of profiles of genes encoding SAgs has been used as an additional epidemiological tool to explore the genomic heterogeneity and possible correlation between toxin gene content and disease type [8].…”
Section: Introductionmentioning
confidence: 99%
“…More broadly, as epidemiological studies of streptococcal disease in developing nations routinely fail to report the presence of traditional ‘rheumatogenic’ emm -types, the concept of ‘rheumatogenic’ emm -types is currently in flux [ 79 ]. In this context, historical rheumatogenic emm -types may have reflected the epidemiology of disease in North America and Europe at the time the studies were conducted [ 80 82 ], but may not be representative of ARF/RHD at a global scale.…”
Section: Discussionmentioning
confidence: 99%